Community engagement initiatives in primary health care to achieve universal health coverage: A realist synthesis of scoping review. - Daniel Erku; Resham Khatri; Aklilu Endalamaw; Eskinder Wolka; Frehiwot Nigatu; Anteneh Zewdie; Yibeltal Assefa (PLoS ONE)
Background Community engagement (CE) is an essential component in a primary health care (PHC) and there have been growing calls for service providers to seek greater CE in the planning, design, delivery and evaluation of PHC services. This scoping review aimed to explore the underlying attributes, contexts and mechanisms in which community engagement initiatives contribute to improved PHC service delivery and the realisation of UHC. Methods PubMed, PsycINFO, CINAHL, Cochrane Library, EMBASE and Google Scholar were searched from the inception of each database until May 2022 for studies that described the structure, process, and outcomes of CE interventions implemented in PHC settings. We included qualitative and quantitative studies, process evaluations and systematic or scoping reviews. Data were extracted using a predefined extraction sheet, and the quality of reporting of included studies was assessed using the Mixed Methods Appraisal Tool. The Donabedian's model for quality of healthcare was used to categorise attributes of CE into "structure", "process" and "outcome". Results Themes related to the structural aspects of CE initiatives included the methodological approaches (i.e., format and composition), levels of CE (i.e., extent, time, and timing of engagement) and the support processes and strategies (i.e., skills and capacity) that are put in place to enable both communities and service providers to undertake successful CE. Process aspects of CE initiatives discussed in the literature included: i) the role of the community in defining priorities and setting objectives for CE, ii) types and dynamics of the broad range of engagement approaches and activities, and iii) presence of an on-going communication and two-way information sharing. Key CE components and contextual factors that affected the impact of CE initiatives included the wider socio-economic context, power dynamics and representation of communities and their voices, and cultural and organisational issues. Conclusions Our review highlighted the potential role of CE initiatives in improving decision making process and improving overall health outcomes, and identified several organisational, cultural, political, and contextual factors that affect the success of CE initiatives in PHC settings. Awareness of and responding to the contextual factors will increase the chances of successful CE initiatives.